Kajian Rekomendasi Pemupukan Tebu dengan Perangkat Uji Hara Tebu di Kabupaten Ogan Ilir Sumatera Selatan - Joni Karman (Seminar Nasional Lahan Suboptimal, 2018)
Karman et al, 2019. Study of Sugar Cane Fertilizer Recommendation with Sugar Cane Nutrient Test Devices in Ogan Ilir District, South Sumatera. pp. 21-27.Increasing productivity can be done with balanced fertilization. This study was conducted to determine the effect of fertilizer dosage and the provision of compost based on the dosage of PUHT fertilization recommendation for the local area. The study was conducted at the location of the farmer’s sugar cane plantation in Ogan Ilir, South Sumatra. The design of study was RAL factorial with 4 replications. The first factor is fertilizer dosage consists of 3 levels, namely 75% dose recommendation; 100% dose recommendation; and 125% dose recommendations. The second factor is the application of compost consisting of 2 levels, namely without compost; and with compost. The results of the study showed that increasing fertilizer dosage recommendations and composting applications provided a significant increase in sugarcane production. However, the increase in production does not directly proportional to the increase in the value of R/C. Fertilization that produces the highest R/C value is 125% dose recommendation without giving compost, it is slightly different with 75% dose recommendation without giving compost.